"Verba dicendi" wśród regresywnych czasowników doby nowopolskiej = "Verba dicendi" as a part of verbs going out of use during the new-polish period - Kwapień, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents verbs of speech falling into oblivion during the new-Polish period. The lexis has been excerpted from "The Dictionary of Polish language" edited by W. Doroszewski. All verbs was identified as "archaic", "obsolete" or "going out of use". The lexis presented in the paper has been devided in semantic fields based on H. Sędziak monograph.
Keywords: leksyka; czasowniki mówienia; doba nowopolska; słownictwo wychodzące z użycia; lexis; verbs of speech; new-Polish period; lexis coming out of use